Developing a Program to Promote Stress Resilience and Self-Care in First Year Medical Students - Thomas, Suzanne; Haney, Myra; Pelic, Chris; Shaw, Darlene; Wong, Jeffrey (Canadian Medical Education Journal, 2011)
Background: Facilitating stress resilience in future physicians is an important role of medical educators and administrators. We developed and piloted an extracurricular program on stress management with first year medical students. Methods: Presentations on topics related to mental health, help-seeking, and stress resilience were presented (one topic per session). Attendance was voluntary. Attendees were requested to complete anonymous evaluations following each presentation. Primary outcome variables were rates of agreement that the presentation (1) was interesting, (2) provided valuable information, and (3) provided information relevant for the student’s future practice as a physician. Results: Each of the seven topics was attended on average by approximately half of the student body. Evaluations were positive in that presentations were interesting and provided information useful to maintaining balance during medical school (all had ? 85% rates of agreement). Evaluations by students were variable (41% - 88% rates of agreement) on whether each presented information relevant for future practice. Conclusions: The results indicate that first-year medical students value explicit guidance on ways to bolster stress resilience and self-care during medical school. It is important to clarify with each presentation how the information is relevant to their future practice as a physician.